Improving the Uptake of Hybrid Life Cycle Assessment in the Construction Industry. (2017) - Bontinck, Paul-Antoine; Crawford, Robert H.; Stephan, André
Abstract: The built environment is responsible for a significant proportion of humanity's pressure on the natural environment. Tremendous amounts of energy, water and materials are necessary for the construction and operation of buildings. The continued growth in global population is expected to only further exacerbate existing environmental concerns. As a key industry, the construction sector needs a better understanding of the environmental implications of decisions made during the design and construction of buildings and other construction projects. Using life cycle assessment, recent research has highlighted the significance of construction-related environmental effects over the whole life cycle of a building. This reinforces the need for a life cycle approach during the design process. Three approaches are currently used to compile a life cycle inventory capturing data on the inputs and outputs associated with a particular good or service: process, input-output and hybrid analysis. While process analysis is the method conventionally used by practitioners, it suffers from a systematically truncated system boundary. Input-output analysis offers a more complete overview of the system, but presents information aggregated for entire economic sectors. Hybrid analysis aims to combine both approaches, mitigating their limitations while retaining their strengths. However, it is still a complex and time-consuming approach, and as such is seldom used outside a narrow area of research. This study explores the potential for automating the hybridisation process using on a conceptual framework developed by the research team. A case study focusing on a construction assembly is used to demonstrate the approach. It suggests that a complete automation of the hybridisation process may be difficult to achieve, but that key steps can be automated. This would accelerate the development and broader update of hybrid inventories for materials and assemblies, a critical step in the uptake of the hybrid analysis method.